Toward a high-precision mass–energy test of the equivalence principle with atom interferometers - Zhou, Lin; Yan, Si-Tong; Ji, Yu-Hang; He, Chuan; Jiang, Jun-Jie; Hou, Zhuo; Xu, Run-Dong; Wang, Qi; Li, Zhi-Xin; Gao, Dong-Feng; Liu, Min; Ni, Wei-Tou; et al. (Frontiers in Physics, 2022)
The equivalence principle (EP) is a basic assumption of the general relativity. The quantum test of the equivalence principle with atoms is an important way to examine the applicable scope of the current physical framework so as to discover new physics. Recently, we extended the traditional pure mass or energy tests of the equivalence principle to the joint test of mass–energy by atom interferometry (Zhou et al.,Phys.Rev.A 104,022822). The violation parameter of mass is constrained to η0 = (−0.8 ± 1.4) × 10–10 and that of internal energy to ηE = (0.0 ± 0.4) × 10–10 per reduced energy ratio. Here, we first briefly outline the joint test idea and experimental results, and then, we analyze and discuss how to improve the test accuracy. Finally, we report the latest experimental progress toward a high-precision mass–energy test of the equivalence principle. We realize atom interference fringes of 2T = 2.6 s in the 10-m long-baseline atom interferometer. This free evolution time T, to the best of our knowledge, is the longest duration realized in the laboratory, and the corresponding resolution of gravity measurement is 4.5 × 10−11 g per shot.